2018
DOI: 10.1111/1752-1688.12658
|View full text |Cite
|
Sign up to set email alerts
|

Reservoir Sedimentation Rates in the Little Washita River Experimental Watershed, Oklahoma: Measurement and Controlling Factors

Abstract: Forty‐five flood control reservoirs, authorized in the Watershed Protection and Flood Prevention Act 1954, were installed by United States Department of Agriculture (USDA) between 1969 and 1982 in the Little Washita River Experimental Watershed (LWREW), located in central Oklahoma. Over time, these reservoirs have lost sediment and flood storage capacity due to sedimentation, with rates dependent on upstream land use and climate variability. In this study, sedimentation rates for 12 reservoirs representing thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 26 publications
0
20
0
Order By: Relevance
“…Cross and Moore () and Furnans and Austin () reported closer transect spacing during a bathymetric survey of waterbodies improved the confidence and accuracy of the estimated water volume. According to Moriasi, Steiner, Duke, Starks, and Verser (), the volume estimated from the 2016 study could have higher accuracy since bathymetric water volume measurements using APS usually have an error value of ± 4.2%.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cross and Moore () and Furnans and Austin () reported closer transect spacing during a bathymetric survey of waterbodies improved the confidence and accuracy of the estimated water volume. According to Moriasi, Steiner, Duke, Starks, and Verser (), the volume estimated from the 2016 study could have higher accuracy since bathymetric water volume measurements using APS usually have an error value of ± 4.2%.…”
Section: Resultsmentioning
confidence: 99%
“…Cross and Moore (2014) and Furnans and Austin (2008) reported closer transect spacing during a bathymetric survey of waterbodies improved the confidence and accuracy of the estimated water volume. According to Moriasi, Steiner, Duke, Starks, and Verser (2018), the volume estimated from the 2016 study could have higher accuracy since bathymetric water volume measurements using APS usually have an error value of ± 4.2%. Thompson and Dodson (1963) and Ase et al (1986) did not specify whether the volumes observed in their studies represented only Lake Naivasha or the combined volume of Lake Naivasha and Lake Oloiden, thereby limiting the comparison of their findings with those of the 2016 survey.…”
Section: Lake Naivasha Volumementioning
confidence: 99%
“…The volumetric lake sedimentation rate (LaSR) was determined from the sediment volume calculated for the 0–20, 20–50 and 0–50 periods. The LaSR was calculated using Equation , which was adopted from Moriasi, Steiner, Duke, Starks, and Verser (), LaSR=SVYrswhere LaSR = volumetric lake sedimentation rate (m 3 /year); SV = sediment volume (m 3 ); and Yrs = number of years under consideration (20, 30, 50 years). Because Lake Naivasha is a natural waterbody, the original volume was not known.…”
Section: Methodsmentioning
confidence: 99%
“…Research Center Walnut Gulch Moran, Emmerich, et al (2009), Moran, Hutchinson, et al (2009) www.tucson.ars. ag.gov/dap/ -Semiarid and monsoon influenced precipitation, runoff, and erosion -Influent hydrologic processes and instrumentation (Goodrich et al, 1997;Osborn et al, 1980;Paige et al, 2003;Polyakov et al, 2010;Renard et al, 2008;Smith et al, 1982 (Bosch et al, 2007(Bosch et al, , 2017Hubbard et al, 2004;Lowrance et al, 1984 (Garbrecht & Starks, 2009;Moriasi et al, 2018;Schoof et al, 1987;Van Liew et al, 2003)…”
Section: Southwest Watershedmentioning
confidence: 99%